Understanding the management organization structure of paprika production areas in Indonesia based on the viewpoint of forthcoming globalization - Yamashita, Ryohei; Zuhdi, Ubaidillah (Universitas Nahdlatul Ulama Surabaya, 2020)
The purpose of this study was to understand the management structure that is developing based on social marketing style within the largest paprika-production areas in Indonesia. Through this research, we aimed to clarify the direction and challenges for future development using the strengths, weaknesses, opportunities, and threats (SWOT) analysis method. A field survey of local farming organizations was conducted on December 2011 at West Bandung Regency, Java, Indonesia. The results show that nearly the entire structure of the system was dedicated to the production and sale of raw paprika without creating any processed product. The counterparties were not corporations but individual buyers. Farming organizations could expand their counterparties to include corporations, but they do not use this strategy because they believe that the production speed of the mature laborers was not sufficient to keep up with market demands, and a rash judgment to expand the management scale would necessarily lead to the degradation of product quality. These farming organizations empirically understand that they could lose counterparties; therefore, they attach greater importance to maintaining faithful counterparties than to attracting new customers.